Bridges to Equality and Access in Health Insurance for Vulnerable Populations - Bharti, Gaurav; Matolia, Manisha (Journal of Neonatal Surgery, 2025)
Healthcare accessibility remains a paramount concern globally, with a particular emphasis on addressing the needs of vulnerable populations. In the Indian context, the intersection of socio-economic disparities, diverse cultural landscapes, and varying health statuses accentuates the challenges faced by vulnerable groups in accessing adequate health insurance coverage. This abstract encapsulates the essence of a comprehensive research study that seeks to unravel the intricacies of health insurance within the context of vulnerable populations in India. Through the adoption of evidence-based policies, improved community involvement, and the promotion of inclusive healthcare practices, society can make noteworthy progress in realizing a healthcare system that puts the needs of every person first, irrespective of their financial situation or demographic background. The government should try to offer medical facilities to its citizens free of cost as it is the duty of the government to protects its citizens from any problems. Healthcare accessibility remains a paramount concern globally, with a particular emphasis on addressing the needs of vulnerable populations. In the Indian context, the intersection of socio-economic disparities, diverse cultural landscapes, and varying health statuses accentuates the challenges faced by vulnerable groups in accessing adequate health insurance coverage. This abstract encapsulates the essence of a comprehensive research study that seeks to unravel the intricacies of health insurance within the context of vulnerable populations in India. Through the adoption of evidence-based policies, improved community involvement, and the promotion of inclusive healthcare practices, society can make noteworthy progress in realizing a healthcare system that puts the needs of every person first, irrespective of their financial situation or demographic background. The government should try to offer medical facilities to its citizens free of cost as it is the duty of the government to protects its citizens from any problems.